COLOR CENTERS INDUCED IN LIF CRYSTALS BY LOW TEMPERATURE ELECTRON IRRADIATION - Nuritdinov, I.; Mussaeva, M.A.; Ibragimova, E.M.; Esanov, Z.U.; Nurimbetov, K.K.; Atashov, B.T. (ILIM hám JÁMIYET, 2025)
The absorption spectra of optical pure LiF crystals were studied after irradiation with 5 MeV electrons at a beam current 400 nA to fluencies 5·10^14 cm^-2 and 10^15 cm^-2 at 165 K and 288 K, which are below and above the temperature of charge carrier release from traps. Immediately after such irradiation, the crystals acquired a bright green coloration, which was stable at 77 K and annealed at 300 K. The absorption spectra contain the known bands of F-centers at 250 nm and F2(M)-centers at 445 nm with their intensity ratio depending on the irradiation temperature. At a higher irradiation dose of 10^15 cm^-2, even at 165 K, which hinders thermal diffusion, the increase in the concentration of F2 centers is sufficient to form larger aggregates of vacancies responsible for M centers of 440 nm and growing absorption bands at 320, 380 nm, as well as Li nanocolloids ( 520, 600, 950 nm).